Remote Ischemic Conditioning May Improve Disability and Cognition After Acute Ischemic Stroke: A Pilot Randomized Clinical Trial - Poalelungi, Alina; Tulbă, Delia; Turiac, Elena; Stoian, Diana; Popescu, Bogdan Ovidiu (Frontiers in Neurology, 2021)
Background and Aim: Remote ischemic conditioning is a procedure purported to reduce the ischemic injury of an organ. This study aimed to explore the efficiency and safety of remote ischemic conditioning in patients with acute ischemic stroke. We hypothesized that remote ischemic conditioning administered from the first day of hospital admission would improve the infarct volume and clinical outcome at 180 days. Material and Methods: We performed a unicentric double-blind randomized controlled trial. We included all patients consecutively admitted to an Emergency Neurology Department with acute ischemic stroke, ineligible for reperfusion treatment, up to 24 hours from onset. All subjects were assigned to receive secondary stroke prevention treatment along with remote ischemic conditioning on the non-paretic upper limb during the first 5 days of hospitalization, twice daily - a blood pressure cuff placed around the arm was inflated to 20 mmHg above the systolic blood pressure (up to 180 mmHg) in the experimental group and 30 mmHg in the sham group. The primary outcome was the difference in infarct volume (measured on brain CT scan) at 180 days compared to baseline, whereas the secondary outcomes included differences in clinical scores (NIHSS, mRS, IADL, ADL) and cognitive/mood changes (MoCA, PHQ-9) at 180 days compared to baseline. Results: We enrolled 40 patients; the mean age was 65 years and 60% were men. Subjects in the interventional group had slightly better recovery in terms of disability, as demonstrated by the differences in disability scores between admission and 6 months (e.g., the median difference score for Barthel was −10 in the sham group and −17.5 in the interventional group, for ADL −2 in the sham group and −2.5 in the interventional group), as well as cognitive performance (the median difference score for MoCA was −2 in the sham group and −3 in the interventional group), but none of these differences reached statistical significance. The severity of symptoms (median difference score for NIHSS = 5 for both groups) and depression rate (median difference score for PHQ-9 = 0 for both groups) were similar in the two groups. The median difference between baseline infarct volume and final infarct volume at 6 months was slightly larger in the sham group compared to the interventional group (p = 0.4), probably due to an initial larger infarct volume in the former. Conclusion: Our results suggest that remote ischemic conditioning might improve disability and cognition. The difference between baseline infarct volume and final infarct volume at 180 days was slightly larger in the sham group.